The apostle : a thriller - Thor, Brad (New York : Pocket Books, 2010)
When American doctor Julia Gallo is kidnapped in Afghanistan, the terms of her ransom leave the president with only one course of action: send covert counterterrorism operative Scot Harvath to free the man the kidnappers demand as ransom.
Keywords: Intelligence officers -- Fiction; Suspense fiction